Molecular engineering of lanthanide ion chelating phospholipids generating assemblies with a switched magnetic susceptibility. Issue 31 (26th July 2017) - Isabettini, Stéphane; Massabni, Sarah; Hodzic, Arnel; Durovic, Dzana; Kohlbrecher, Joachim; Ishikawa, Takashi; Fischer, Peter; Windhab, Erich J.; Walde, Peter; Kuster, Simon
Abstract : Molecular engineering of lanthanide ion chelating phospholipids generating novel polymolecular assemblies with a switched magnetic susceptibility Δ χ and alignment direction. Abstract : Lanthanide ion (Ln 3+ ) chelating amphiphiles are powerful molecules for tailoring the magnetic response of polymolecular assemblies. Mixtures of 1, 2-dimyristoyl- sn-glycero -3-phosphocholine (DMPC) and 1, 2-dimyristoyl- sn-glycero -3-phospho-ethanolamine-diethylene triaminepentaacetate (DMPE-DTPA) complexed to Ln 3+ deliver highly magnetically responsive bicelles. Their magnetic properties are readily tuned by changing the bicellar size or the magnetic susceptibility Δ χ of the bilayer lipids. The former technique is intrinsically bound to the region of the phase diagram guarantying the formation of bicelles. Methods aiming towards manipulating the Δ χ of the bilayer are comparatively more robust, flexible and lacking. Herein, we synthesized a new Ln 3+ chelating phospholipid using glutamic acid as a backbone: DMPE-Glu-DTPA. The chelate polyhedron was specifically engineered to alter the Δ χ, whilst remaining geometrically similar to DMPE-DTPA. Planar asymmetric assemblies hundreds of nanometers in size were achieved presenting unprecedented magnetic alignments. The DMPE-Glu-DTPA/Ln 3+ complex switched the Δ χ, achieving perpendicular alignment of assemblies containing Dy 3+ and parallel alignment of those containing Tm 3+ . Moreover, samples with chelated Yb 3+ were more alignable than the Tm 3+ chelating counterparts. Such a possibility has never been demonstrated for planar Ln 3+ chelating polymolecular assemblies. The physico-chemical properties of these novel assemblies were further studied by monitoring the alignment behavior at different temperatures and by including 16 mol% of cholesterol (Chol-OH) in the phospholipid bilayer. The DMPE-Glu-DTPA/Ln 3+ complex and the resulting assemblies are promising candidates for applications in numerous fields including pharmaceutical technologies, structural characterization of membrane biomolecules by NMR spectroscopy, as contrasting agents for magnetic resonance imaging, and for the development of smart optical gels.